Low-Temperature Clay Mineral Dehydration Contributes to Porewater Dilution in Bering Sea Slope Subseafloor - Ijiri, Akira; Tomioka, Naotaka; Wakaki, Shigeyuki; Masuda, Harue; Shozugawa, Katsumi; Kim, Sunghan; Khim, Boo-Keun; Murayama, Masafumi; Matsuo, Motoyuki; Inagaki, Fumio (Frontiers in Earth Science, 2018)
Widespread diagenesis of clay minerals occurs in deeply buried marine sediments under high-temperature and high-pressure conditions. For example, the smectite-to-illite (S-I) transformation has been often observed in sediments at in situ temperatures above ~60°C. However, it remains largely unknown whether such diagenetic processes naturally occur in relatively shallow and low-temperature sediments and, if so, what the consequences are of any related chemical reactions to the geochemical characteristics in the deep biosphere. We evaluated the possibility of naturally occurring S-I transformation at temperatures below 40°C in continental slope sediments of the Bering Sea by examining porewater chemistry, clay mineralogy, and chemical composition of clay minerals measured to ~800 m beneath the seafloor (mbsf) in core samples acquired during Integrated Ocean Drilling Program Expedition 323. In porewater from these cores, chloride concentrations decreased with increasing depth from 560 mM near the seafloor to 500 mM at ~800 mbsf; δ18O increased from 0‰ to 1.5‰; and δD decreased from –1‰ to –9‰. These trends are consistent with the addition of water derived from S-I transformation. The discrete low Cl– spikes observed between ~200 mbsf and ~450 mbsf could be attributed to the dissociation of methane hydrate. X-ray diffraction analysis of the clay-size fraction (<2 µm) showed an increase of illite content in the I/S mixed layer with increasing depth to 150 mbsf. This increase may imply the occurrence of S-I transformation. The decrease of Fe3+/Fe2+ in the clay-size fraction with increasing depth strongly suggests microbial reduction of Fe(III) in clay minerals with burial, which also has the potential to promote the S-I transformation. Our results imply the significant ecological roles on the diagenesis of siliciclastic clay minerals underlying the high-productivity surface seawater at continental margins.